2019
DOI: 10.3122/jabfm.2019.03.180288
|View full text |Cite
|
Sign up to set email alerts
|

Provider Perspectives of Patient Experiences in Primary Care Imaging

Abstract: Background: Imaging tests are a widely used tool in primary care with many known benefits. Without an understanding of which outcomes matter the most to patients, clinicians are challenged to balance the benefits and harms of imaging tests. This study aimed to explore the perceived impacts imaging tests have on patients from the perspective of the primary care providers (PCPs) and determine PCPs' understanding of patient-centered outcomes (PCOs) from imaging tests.Methods: Recruitment of PCPs occurred at 4 fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…13 Primary care providers were able to connect the outcome pathways a bit more and reported that the answers provided from imaging tests influenced emotional outcomes and that there is additional burden on the patient from added testing, monetary and physical risks. 18 This evidence of triangulation from the four perspectives strengthens support for the occurrence and potential importance of these outcomes among patients undergoing imaging testing. 13 18 Indeed, previous research has highlighted the importance of psychosocial/emotional outcomes (often described as stress, anxiety or reassurance), [22][23][24] as well as physical impacts of tests (including comfort/discomfort) 25 and the value of information to patients such as knowledge about the test, awareness of harms, value (or lack of value) of knowing test findings.…”
Section: Open Accessmentioning
confidence: 69%
“…13 Primary care providers were able to connect the outcome pathways a bit more and reported that the answers provided from imaging tests influenced emotional outcomes and that there is additional burden on the patient from added testing, monetary and physical risks. 18 This evidence of triangulation from the four perspectives strengthens support for the occurrence and potential importance of these outcomes among patients undergoing imaging testing. 13 18 Indeed, previous research has highlighted the importance of psychosocial/emotional outcomes (often described as stress, anxiety or reassurance), [22][23][24] as well as physical impacts of tests (including comfort/discomfort) 25 and the value of information to patients such as knowledge about the test, awareness of harms, value (or lack of value) of knowing test findings.…”
Section: Open Accessmentioning
confidence: 69%